Knowledge, Attitude, and Practice of Postexposure Prophylaxis against HIV Infection among Healthcare Workers in Hiwot Fana Specialized University Hospital, Eastern Ethiopia - Endalkachew Mekonnen Eticha; Ashenafi Beru Gemeda (AIDS Research and Treatment)
Background. Postexposure chemoprophylaxis can prevent human immunodeficiency virus (HIV) infection in risk health care workers; however routine adoption of these practices by the workers has been limited. Methods. A cross-sectional study was conducted on 311 health care workers of Hiwot Fana Specialized University Hospital between February and March 2016. Data was collected using a structured self-administered questionnaire and analysed using STATA 12. Results. In all, 83% of the participants had adequate knowledge of postexposure prophylaxis for HIV. All the respondents had heard about postexposure prophylaxis for HIV; however, only 37 (22.4%) workers know the definition of the postexposure prophylaxis. Among study participants, the majority of them, 272 (87.5%), knew the preferable time to initiate postexposure chemoprophylaxis. A significant number of the workers (43.4%) had an unfavorable attitude towards postexposure prophylaxis. Among 53 workers with a potential exposure to HIV, 38 (71.7%) took postexposure chemoprophylaxis and only 26 (44.8%) completed taking postexposure prophylaxis correctly. Conclusion. In all, most of the health care workers had adequate knowledge about postexposure prophylaxis against HIV/AIDS. The result shows that a significant number of individuals had a negative attitude and poor practice with regard to postexposure prophylaxis. Therefore, formal training that aims to improve attitudes and support to improve postexposure prophylaxis implementation and completion are needed. We would recommend the establishment of appropriate guidelines and the supply chain to ensure the availability of postexposure prophylaxis drugs for the protection of healthcare workers with potential high risk exposure to HIV.